Book review: Michael Calabrese, An Introduction to “Piers Plowman” (Gainesville, FL: University Press of Florida 2016), xxx + 355 pp. - Glover, T (UCLA Center for Medieval and Renaissance Studies, 2017)
An Introduction to “Piers Plowman” provides a sophisticated and accessible guide for students who are beginning to study Langland’s sprawling masterpiece. Buoyed by his obvious enthusiasm for the poem, Michael Calabrese gives clarity to the poem’s frequently disorientating narrative, analyses its political and social commentary, and cajoles his readers into appreciating the poem’s artistry.